Study on Public Understanding and Application of Green Property Concepts in the Code Riverbank Settlements of Yogyakarta - Ratnawati Yuni Suryandari; Ken Martina Kasikoen; Elsa Martini (Journal of Creative Power and Ambition (JCPA), 2026)
Village planning efforts in the context of green property development on the banks of the Code River in Yogyakarta have been ongoing for decades and continue to this day. This village planning is crucial for reducing disaster risks and improving the community's quality of life. The purpose of this study was to identify the level of community participation in green property development along the banks of the Code River in Yogyakarta and to examine the factors influencing their participation. This research was quantitative. Primary data were collected from a questionnaire regarding the level of community participation in green property development using Likert scale analysis and quantitative descriptive analysis. Sampling was conducted using random sampling of 100 respondents. The results showed that although most people are aware of green property, their level of understanding is still relatively low. Cost and lack of information are the main obstacles to increasing community participation. Environmental benefits are the most motivating factor for community involvement in this development. Although the green property concept has been implemented, its adoption rate is still relatively low and tends to be limited to features that are easier to implement. Further encouragement is needed to encourage more homes to implement the principles of sustainability and resource efficiency in their construction. To increase the adoption of green property on the banks of the Code River, a combination of education, economic incentives, supportive regulations, and active community involvement is needed.